Statistics in natural resources applications with R - Russell, Matthew A. (Computer scientist) (CRC Press, 2023)
To manage our environment sustainably, professionals must understand the quality and quantity of our natural resources. Statistical analysis provides information that supports management decisions and is universally used across scientific disciplines. Statistics in Natural Resources: Applications with R focuses on the application of statistical analyses in the environmental, agricultural, and natural resources disciplines. This is a book well suited for current or aspiring natural resource professionals that are required to analyze data and perform statistical analyses in their daily work. More seasoned professionals that have previously had a course or two in statistics will also find the content familiar. This book can also serve as a bridge between professionals that understand statistics and want to learn how to perform analyses on natural resources data in R"--